Construção e análise de desempenho de um forno/fogão solar tipo caixa construído a partir de uma sucata de pneu - Gomes, Jailton Weber (2009)
An alternative box-type solar cooker built starting from the scrap of a tire and a scrap of old office chair is presented, which principles functions are the effect greenhouse and the concentration. The tire served as structure for making of is the baking enclosure where the absorber (roasting pan 20x30cm) of the solar is located, being re-covered for a glass blade for the generation of the greenhouse effect isolated lateral and having deep its and for a composite the plaster base and EPS. Segments of plain mirrors had been placed in the laterals of the oven/cook for the concentration of the radiation and a reflecting parable was introduced in the baking enclosure for the exploitation of the incident reflected radiation inside of the oven/cook. The oven/cook is mobile to allow one better aiming of exactly in relation to the apparent movement of the sun. The thermal economic and of materials viabilities of the stove/cook in study will be demonstrate. The average internal temperature of the absorber was around 152,3°C and the internal temperature around 110°C. Will demonstrate that toits low cost and good thermal performance, represents basic characteristics for the viability of large use of such archetype, mainly for cooking the decreases and averages temperatures. One will reveal that the archetype in study is competitive with the box-type solar cooker conceived in the whole world